The Influence of Transformational Leadership and Oganization Culture on The Peformance of Stockfit Employees at PT Adis Dimension Footwear Tangerang Regency - Rizal, Samsul; Purwanto, Agus; Setiawan, Temmy (UJoST- Universal Journal of Science and Technology, 2026)
This study aims to determine the simultaneous influence of transformational leadership and organizational culture on the performance of employees in the Stockfit department at PT Adis Dimension Footwear Balaraja-Tangerang.This study used a quantitative descriptive method, and the population comprised all employees at PT Adis Dimension Footwear Balaraja-Tangerang. The sample size was 81 respondents. Simple random sampling was used to determine the sample size. The Slovin formula was used to determine a representative sample size in quantitative research. Data analysis used multiple linear regression analysis using SPSS 26.The results of this study indicate that (1) partially, transformational leadership significantly influences the performance of employees in the Stockfit department at PT Adis Dimension Footwear Balaraja-Tangerang, as indicated by the calculated t-value > t-table (2.209 > 1.990), and a significance value of 0.000, which is less than the 0.05 threshold. Therefore, Ha is accepted and H0 is rejected. (2) Partially, organizational culture significantly influences the performance of Stockfit employees at PT. Adis Dimension Footwear Balaraja-Tangerang, as indicated by the calculated t value > t table (10.024 > 1.990) and a significance value of 0.000 smaller than the significance value of 0.05. Thus, Ha is accepted and H0 is rejected. (3) Simultaneously, transformational leadership and organizational culture significantly influence the performance of Stockfit employees at PT. Adis Dimension Footwear Balaraja-Tangerang, as indicated by the calculated F value > F table (334.900 > 3.11) with a significance level of 0.000. Thus, Ha is accepted and H0 is rejected.Based on the results of the study, it can be concluded that the variables of transformational leadership and organizational culture, both partially and simultaneously, have a significant influence on the performance of Stockfit employees at PT. Adis Dimension Footwear Balaraja-Tangerang.